Introduction: Ludic Seriality, Digital Seriality - Denson, Shane; Jahn-Sudmann, Andreas (Eludamos: Journal for Computer Game Culture, 2014)
Special issue on Digital Seriality. Please click on the links below for HTML or PDF versions of the introduction.